Model Komunikasi Kepala Desa dalam Meningkatkan Partisipasi Masyarakat - Fachri Zidan Al Haris; Alfina Nur Amalia (Al-Balagh : Jurnal Komunikasi Islam, 2023)
This study aims to find a model of communication and its types, it is equally known that if humans as individual beings and social beings, have the urge to know, want to progress and develop, then one of the means is communication. Therefore communication is a necessity absolute for human life. The village head is the head of government at the village level who is able to run the wheels of village governance well in providing services to the community, so that the village head shows good performance in the implementation of village governance, so it will also affect the performance of government at the district, provincial, and central levels. The village head as a leader in the village scope has personality aspects and leadership processes that can support his efforts to create good relationships with members of his community. The leadership process carried out by the village head is very close to the goals achieved by a village government. Therefore, the village head leadership process always provides the village head's activities in directing, motivating, communicating, making decisions, and supervising members to realize the goals of village governance.